ANALISIS PERENCANAAN PENGAJARAN DAN PERFORMANCE GURU DI MTS MIFTAHUL JANNAH KECAMATAN PERANAP - Rino Yurizal (AL-HIKMAH (Jurnal Pendidikan dan Pendidikan Agama Islam), 2020)
Teaching planning is a process and way of thinking that can help create the expected learning outcomes while teacher performance is an appearance which means the process, method, and actions performed by a teacher. Based on the results of observations at MTs Miftahul Jannah Kecamatan Peranap teacher has made a teaching plan that is contains Prota, Promes, Syllabus, RPP, evaluation tools, which are contained in the administration of teacher learning tools, but in the learning process carried out by the teacher at MTs Miftahul Jannah is still not good, then teacher performance and the methods used by the teacher are not in accordance with the planning As for the formulation of the problem in this research is how the planning of teacher teaching at MTs Miftahul Jannah, Peranap sub-district and the factors that affect the planning of teacher teaching at MTs Miftahul Jannah, Peranap district. The population in this study were teachers of MTs Miftahul Jannah, Peranap District. And the sample consisted of 20 teachers at MTs Miftahul Jannah, Peranap District. This research includes research with a quantitative descriptive approach, with data collection techniques through questionnaires, interviews and observations. And the data analysis techniques used were data reduction, data presentation and drawing conclusions. The results showed that in the planning of teaching by the teacher at MTs Miftahul Jannah, Peranap District was classified as "Good" with a percentage of 80.4% and the teacher's performance at MTs Miftahul Jannah Kecamatan Peranap was classified as " Not good ”with a percentage of 47.6%. The factors of analysis of teaching planning and teacher performance at MTs Miftahul Jannah Kecamatan Peranap are factors of teacher education level and principal innovation factors. Keywords: Analysis of Teaching Planning and Teacher Performance at MTs Miftahul Jannah, Kecamatan Peranap